If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + 7 = 84 + -6y Reorder the terms: 7 + 5y = 84 + -6y Solving 7 + 5y = 84 + -6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6y' to each side of the equation. 7 + 5y + 6y = 84 + -6y + 6y Combine like terms: 5y + 6y = 11y 7 + 11y = 84 + -6y + 6y Combine like terms: -6y + 6y = 0 7 + 11y = 84 + 0 7 + 11y = 84 Add '-7' to each side of the equation. 7 + -7 + 11y = 84 + -7 Combine like terms: 7 + -7 = 0 0 + 11y = 84 + -7 11y = 84 + -7 Combine like terms: 84 + -7 = 77 11y = 77 Divide each side by '11'. y = 7 Simplifying y = 7
| 14-8x=132-36x | | 5+9y=77+y | | -130-9x=8x+24 | | 4y-3=12y-75 | | 2x+12=-38-8 | | 2y+34=11y-38 | | log[2]8=x | | y=(7+2k)x | | 2x+34=11y-38 | | 5x+5=82-6 | | 10y-9=8y+1 | | 6y+59=11y+14 | | 12y+7=9y+28 | | log[2](9x+1)=x | | 10y-5=95 | | 4x^2y^2-9x^2=0 | | 49x^2y^2+7x^2y+x^2=0 | | 343x^2y^3-x^2=0 | | 8x^2y^3+27x^2=0 | | .05x+40=.15x | | -3x+5x=-8+6+9x | | -16t^2+96t+176=0 | | 3x^5-13x^4-29x^3+83x^2+66x-30=0 | | x^4-2x^2(x-2)+x^2-4x+4= | | 24=18-2g | | t^2-6t-11=0 | | 44-4h=12 | | 2+4x=-16 | | x=(x+1)(x+3) | | 91-x=171 | | x=x+1x+3 | | x^2+8ix-16=0 |